Effective sericin-fibroin separation from Bombyx mori silkworms fibers and low-cost salt removal from fibroin solution (2020)
ABSTRACT : Silk from Bombyx mori has two main proteins: fibroin and sericin. Fibroin is a protein that exhibits good biocompatibility and high surface reactivity, desirable properties for many biomedical applications. Sericin is related with adverse immune response in some medical uses. Therefore, its removal (degumming) is desirable in almost all fields, including the textile industry and biological applications. In this study, three degumming methods (distilled water, liquid neutral detergent and sodium carbonate solution) were evaluated using Raman spectroscopy. Degummed silk treated with sodium carbonate solution exhibits a pattern consistent with previous studies for sericin-free fibroin, and significant differences with the untreated silk pattern. Also, degummed fibroin fibers were dissolved in a calcium chloride solution, in pursuit of a more versatile material. Additionally, different porous membranes of dialysis tubes were tested to remove residual salts, and were compared by conductivity measurements and EDS analysis, identifying good performance for an affordable food cellulose membrane. The results showed that it is possible to obtain fibroin with adequate chemical properties, using low-cost process and membrane of dialysis tubes.